Music and dance in mammals - Lidicker, William (THERYA, 2019)
A long-standing belief among humans is that the behaviors we call making music and dancing are thought to be strictly human activities. Rapidly accumulating evidence, however, tells a different story. Both music and dance are characterized by sensitivity to and moving in response to rhythms. Among humans, these two behaviors are ubiquitous in all living cultures and can be traced back in our Neanderthal ancestors at least 50,000 years, and probably much longer. It is well established that in humans these two rhythmic behaviors play important social functions, and in recent years have been increasingly noted as well for their health benefits. All of this has called attention to similar behaviors in non-humans. Many examples have been noted among mammals, birds, reptiles, amphibians and even bony fish. Neurologists became interested in understanding the neural mechanisms for these rhythmic behaviors and found that rhythmic behaviors are organized in one of the most ancient parts of the vertebrate brain, namely the subcortical posterior parietal cortex which is located just on top of the uppermost ending of the spinal cord. This anatomy was then found to be the same in almost all vertebrates going back in history for many millions of years to the bony fish. So, now it is understandable why music and dance are so widespread among the vertebrates and why there seems to be the potential for these rhythmic behaviors to appear in most of the vertebrates. This discovery also emphasizes the potential availability of the beneficial effects of these behaviors. Needless to say, there is also the prospect of an emerging opportunity for much exciting and important research on mammals.